Influência da época de semeadura sobre cultivares de soja em safra de La Ninã no noroeste do Rio Grande do Sul - Paraginski, Pedro Elmar (2023)
In view of the great economic and nutritional importance of soybean, the objective was to evaluate the influence of the sowing season on the productive components and grain yield of soybean cultivars sown in the northwest region of Rio Grande do Sul during the 2021/22 harvest. For this, 15 soybean cultivars were used (NS 5505 I2X, NS 6446 I2X, NS 6299 IPRO, NS 5700 IPRO, NS 6010 IPRO, DM 57I52 IPRO, BMX ZEUS IPRO, BMX LANÇA IPRO, BMX TORQUE I2X, BMX CROMO TF IPRO, BMX LÓTUS IPRO, TMG 71X57 I2X, TMG 2359 IPRO, TMG 2356 IPRO, TMG 7260 IPRO) and four sowing seasons (10/21, 11/01, 11/15 and 11/29/2021) in randomized block design with three repetitions. The cultivars NS 6446 I2X and BMX LÓTUS IPRO resulted in the highest grain yields (1466.38 and 1464.42 kg ha-1, respectively), even in the face of adverse weather conditions witnessed in the northwest region of Rio Grande do Sul during the 2021/22 harvest. The first sowing season (10/21/2021) severely affected soybean cultivars, compromising both productive components and grain yield, especially the percentage of viable grains. The fourth sowing season (11/29/2021) resulted in the highest grain yields, mainly due to the higher numbers of pods and grains per plant observed. Cultivars with longer relative maturity cycle resulted in the best results, so that it is recommended the cultivation of these in harvests where there is a greater tendency for the occurrence of the La Niña climatic event.